Estimating Scabies Severity by Epidemiological and Clinical Survey of Baghdad Governorate Patients and Assessing Blood Immune Antibody Levels - Wasan Addai Al-marsomy (Iraqi Journal of Science, 2026)
Scabies is a parasitic infestation caused by tiny mites Sarcoptes scabiei. Scabies can lead to skin ulcers and serious complications such as septicemia (bloodstream infection), heart disease and kidney problems. Therefore, scabies is considered a dangerous infectious disease that must be treated when diagnosed. The current study aimed to conduct a survey of scabies patients of both genders, examining the role of humoral immunity by estimating certain immunoglobulins (IgM and IgG) and their effect on the patients. However, this study involved the collection of blood specimens from a group of 67 patients with scabies and a control. The results showed infected male more than female with a non-significant difference, the values were 20 (57.14%) and 15 (42.86%) respectively, and the largest age group affected of 40 was 5 (14.29%), the majority of those infected were primary school students (12, 34.4%), while the lowest percentage were university graduates (6, 17.1%). Regarding the patient's job, the most affected group was freelancers, at 15 (42.8%), while the lowest percentage was among housewives, at 3 (8.7%). Additionally, the results showed a high significance between patients from agricultural cities and those from civilian towns, with percentages of 23 (65.7%) and 12 (34.3%), respectively. Although most cases of infection were of the mild and papular type 22 (62.8%) and 23 (65.7%), respectively, more than severe and nodular type 13(37.2%) and 12 (34.3%), respectively, the affected area of patients was the entire body (more than three affected organs) in high percentage (15, 42.8%), whereas the lowest value of slight area was 4 (11.5%). Finally, the immunological results showed an increase in the IgM levels in the scabies patients (3.809 ± 0.23) compared to the healthy group (1.269 ± 0.06), and the results also showed an increase in the IgG levels in the patients (12.51 ± 0.53) compared to the healthy group (7.61 ± 0.28).